(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Hyponatremia is the most common electrolyte abnormality seen in patients with aneurysmal SAH. Clinically significant hyponatremia (Serum Sodium <135 mEq/L) requires treatment and there is a paucity of outcome studies based on this. Materials and Methods: This prospective study was undertaken in the Department of Neurology, BSMMU. Patients with aneurysmal subarachnoid hemorrhage (SAH) were selected for this study from 1stJanuary 2020 to 31st October, 2022. Results: A total of 64 patients were included in the study. Hyponatremia was observed in 24 (37.5%) patients. Among them, 14 (58.7%) developed hyponatremia within the first week after SAH. Serum osmolality was low in 70.8% of patients who developed hyponatremia. Urinary osmolality was also high for the same number (70.8%). Low serum osmolality and high urine osmolality were significantly (p<0.05) higher than that of normal values of serum and urine osmolality in hyponatremia patients. Conclusion: Hyponatremia is common after subarachnoid hemorrhage. SIADH is the commonest cause of hyponatremia after subarachnoid hemorrhage.